5D total scattering computed tomography reveals the full reaction mechanism of a bismuth vanadate lithium ion battery anode. Issue 44 (3rd November 2022) - Sottmann, Jonas; Ruud, Amund; Fjellvåg, Øystein S.; Vaughan, Gavin B. M.; Di Michel, Marco; Fjellvåg, Helmer; Lebedev, Oleg I.; Vajeeston, Ponniah; Wragg, David S.
Abstract : 5D operando total scattering computed tomography reveals the mechanism of a lithium ion battery electrode which operates by both alloying and conversion reactions, both at the atomic and the microscopic scale. Abstract : We have used operando 5D synchrotron total scattering computed tomography (TSCT) to understand the cycling and possible long term deactivation mechanisms of the lithium-ion battery anode bismuth vanadate. This anode material functions via a combined conversion/alloying mechanism in which nanocrystals of lithium–bismuth alloy are protected by an amorphous matrix of lithium vanadate. This composite is formed in situ during the first lithiation of the anode. The operando TSCT data were analyzed and mapped using both pair distribution function and Rietveld methods. We can follow the lithium–bismuth alloying reaction at all stages, gaining real structural insight including variations in nanoparticle sizes, lattice parameters and bond lengths, even when the material is completely amorphous. We also observe for the first time structural changes related to the cycling of lithium ions in the lithium vanadate matrix, which displays no interactions beyond the first shell of V–O bonds. The first 3D operando mapping of the distribution of different materials in an amorphous anode reveals a decline in coverage caused by either agglomeration or partial dissolution of the active material, hinting at the mechanism of long term deactivation. The observations from the operando experiment are backed up by post mortem transmission electron microscope (TEM) studies and theoretical calculations to provide a complete picture of an exceptionally complex cycling mechanism across a range of length scales.